Organização argumentativa e gênero no discurso político de posse : teorias em interação - Barros, Rogenildo Andrade (2010)
Situated work in the intersectionof two disciplines- Analysis of the Pragmatic Speech and, aiming at to analyze argumentative organization of the speech ownership politician. The presupposition of that has as research hypothesis the DPP, independent by the partisan filiations that of the support, presents the same argumentative organization, searchs It takes as corpus the speech of ownership of the Governor of State of Sergipe: Marcelo Déda (PT) and the speech of ownership of Governor of State of Paraná, Roberto Requião (PMDB). It uses as theoretical support Searle (1981 and 2002), Austin (1990), Levinson (1989), Armengaud (2006), Brandão (2004), Orlandi (1990, 2005 and 2005b), Ferreira (2005), Pêcheux (2002), Althusser (1998) e Foucault (2007), Amossy (2005), Motta e Salgado (2008), Maingueneau (2008) e Charaudeau (2006), Osakabe (2002), Bakhtin (2000), Marcuschi (2005), Bazerman (2005) e Meurer (2002). It characterizes the DPP while independent literal sort, used in a specific communicative situation, displays the theories that had guided the analysis, make the analysis of the categories mentioned above, dive these categories in the argumentative organization proposal for Osakabe and conclude ratifying the initial hypothesis.